2009
DOI: 10.4049/jimmunol.0803777
|View full text |Cite
|
Sign up to set email alerts
|

A Role of IgM Antibodies in Monosodium Urate Crystal Formation and Associated Adjuvanticity

Abstract: Uric acid is released from injured cells and can act as an adjuvant signal to the immune system. Uric acid crystals invoke strong inflammatory responses in tissues. Although their biological effects are evident and the associated signaling mechanisms are becoming clear, it remains unexplained as to why uric acid precipitates rapidly in vivo, in sharp contrast to the minimal crystallization in vitro. We report in this study that a group of IgM Abs is able to bind to these crystals, which is interesting in light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 44 publications
2
49
0
2
Order By: Relevance
“…One can imagine that sufficient uric acid to induce endogenous inflammatory responses only occurs with large-scale cell death and must be associated with uric acid precipitation; in other words, a general antioxidant is converted into a strong inflammatory stimulant only upon its phase transition (6). Although the work of Kono et al did not address this specific issue (5), recent data have suggested that serum antibodies against uric acid may facilitate its crystallization (17).…”
Section: Not So Trivial Triviamentioning
confidence: 69%
“…One can imagine that sufficient uric acid to induce endogenous inflammatory responses only occurs with large-scale cell death and must be associated with uric acid precipitation; in other words, a general antioxidant is converted into a strong inflammatory stimulant only upon its phase transition (6). Although the work of Kono et al did not address this specific issue (5), recent data have suggested that serum antibodies against uric acid may facilitate its crystallization (17).…”
Section: Not So Trivial Triviamentioning
confidence: 69%
“…Terkeltaub showed that the inflammatory response to MSU crystals could be inhibited by apo B lipoprotein (50). Kanevets et al have recently demonstrated substantial amounts of uric acid-binding antibodies in unimmunized mice (51), and Ig-coated MSU crystals have been observed in gout specimens (summarized in Kanevets,ref. 51).…”
Section: Discussionmentioning
confidence: 99%
“…51). Uric acid-binding antibodies facilitated urate crystal formation but did not block uric acid-mediated activation of dendritic cells (51). Further work is indicated to evaluate for the presence of uric acid-binding antibodies in OA synovial fluids as another possible potentiator of crystal formation.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, natural IgM reduces the inflammatory response by removing the apoptotic cells and preventing inflammatory arthritis (121) and atherosclerosis (91). On the other hand, natural IgM enhances inflammation through increasing the precipitation of urate crystals, which recruits neutrophils and worsens inflammation (122). Natural IgM is also involved in ischemia-reperfusion injury, including myocardial infarction and intestinal ischemia-reperfusion injury, wherein it targets autoantigen-expressing endothelial cells (123,124).…”
Section: Implications Of Natural Abs In Autoimmunity and Inflammatorymentioning
confidence: 99%